Detection of balance in the elderly under the influence of stress (DEPIE): A cross-sectional study protocol - Bernardo Alarcos; Belén Díaz-Pulido; Olalla Fernández; Sara Fernández-Guinea; Antonio García Herraiz; María del Mar Lendínez-Chica; Javier Martínez Muela; Susana Nunez-Nagy; Yolanda Pérez-Martín; Isabel Rodríguez-Costa; Gloria M. Rubio González; Sara Trapero-Asenjo; et al. (PLoS ONE, 2026)
Age-related changes increase frailty and vulnerability to stress in older adults, and stress has been linked to poorer balance and fall risk. However, the mechanisms by which emotional stress may contribute to falls remain unclear. This study explores whether: 1) emotional stressors lead to neuromuscular changes that affect postural control in older adults; and 2) technology can assist in fall prevention by detecting increased risk. A cross-sectional, laboratory-based observational study is being conducted in a single session comparing 30 young adults (18–39 years) and 30 older adults (≥65 years), in which participants are exposed to emotional stressors (high-arousal images) and their immediate neuromuscular and balance responses are recorded. The first participant was enrolled on November 27, 2024. All participants complete a sequence of physical tasks under two conditions: viewing low-arousal and high-arousal images from the International Affective Picture System. The physical tasks involve standing up from a chair, walking to a table, transferring water between bottles, returning to the chair, and sitting down. Emotional responses are assessed using heart rate variability, respiratory rate and subjective feelings of unease. Electromyographic signals are analysed using wearable sensors, ground pressure is recorded via pressure sensors and bottle manipulation is tracked with inertial measurement units. Furthermore, balance is evaluated using the Timed Up and Go Test and the Functional Reach Test, administered before the low-arousal condition and after the high-arousal condition. Comprehensive data analysis will provide new insights to aid professionals in designing interventions for detecting and preventing fall risk in older adults. The study was approved by the corresponding ethics committee and registered at ClinicalTrials.gov (NCT06682754) on November 21, 2024. It is being conducted at the University of Alcalá, Spain, and is funded by the European Union and the ‘Junta de Castilla-La Mancha’. Principal investigators are Dr. Bernardo Alarcos and Dr. Susana Nunez-Nagy ( susana.nunez@uah.es ). The collected data will be anonymized and shared in an open-access repository, in line with ethical and open science principles.